Strindberg and Autobiography - Robinson, Michael (Ubiquity Press, 2013)
This is a book about Strindberg and about the nature of autobiographical writing. In this sensitive and discerning study, Michael Robinson has turned aside from the more traditional biographical approach to Strindberg. Instead he sets out to explore the highly idiosyncratic way in which Strindberg projected himself in language, looking at the problems which this brought in its trail, and laying bare the subterfuges it engendered. He has not limited himself to those works explicitly designated by Strindberg as autobiographical, but ranges widely over the dramas, the narratives and other prose works. (DOI: 10.5334/bab)